2018
DOI: 10.1111/ecc.12968
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ management of cancers in Australian adolescents and young adults

Abstract: General practitioners (GPs) are often the first point of contact adolescents and young adults (AYAs, aged 10–29) with cancer have with the health system, and they are well‐placed to coordinate their complex medical and psychosocial care. This study is the first to report characteristics of patients, GPs and cancers involved in AYA cancer management consultations in Australia, using data from a nationally representative sample of 972,100 patient‐GP encounters in 2006–2016. AYA cancers were managed in 212 encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…PCP roles and responsibilities : Perceived roles of PCPs for AYAs with chronic conditions who had received (or were receiving) specialist care were described in 18 studies (7 quantitative 23,35,47,50,59,60,79 ; 11 qualitative), 55,61,64,66-71,73 which included the perspectives of AYAs and/or their caregivers (n = 6), 37,68-70,73,75 specialist providers (n = 4), 63,67,68,70 and family physicians (FPs) themselves (n = 14). 37,52,61,64-68,70-72,74-76 Common responsibilities of PCPs included: medication management (specifically prescribing and counseling), 35,52,61,64,67,70,71 making referrals to specialists and/or community resources, 35,64,70,71,73 managing mental health problems until more specialized services were needed or became available, 35,61,70,71 serving as care coordinator when multiple services/providers were invol...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCP roles and responsibilities : Perceived roles of PCPs for AYAs with chronic conditions who had received (or were receiving) specialist care were described in 18 studies (7 quantitative 23,35,47,50,59,60,79 ; 11 qualitative), 55,61,64,66-71,73 which included the perspectives of AYAs and/or their caregivers (n = 6), 37,68-70,73,75 specialist providers (n = 4), 63,67,68,70 and family physicians (FPs) themselves (n = 14). 37,52,61,64-68,70-72,74-76 Common responsibilities of PCPs included: medication management (specifically prescribing and counseling), 35,52,61,64,67,70,71 making referrals to specialists and/or community resources, 35,64,70,71,73 managing mental health problems until more specialized services were needed or became available, 35,61,70,71 serving as care coordinator when multiple services/providers were invol...…”
Section: Resultsmentioning
confidence: 99%
“…The longest observation window (16 years) was reported in 1 longitudinal study 44 of children with congenital heart disease, followed from age 6 to 22; these children were more likely to visit their PCP than their cardiologist over time and their frequency of specialist visits decreased as they became older. Finally, characteristics of AYAs more likely to be seen by a PCP during the transition period included: being female, 24 non-Black, 33 older, 24,79 and greater disease severity/complexity (eg, greater number of cancer relapses, 24 increased pain severity, 51 mental health comorbidity). 34 Transfer or discharge from pediatric services: Five intervention studies [28][29][30]38,39 reported rate of transfer to a PCP among AYAs discharged from pediatric services.…”
Section: Table 1 (Continued)mentioning
confidence: 99%